Time to Adjuvant Chemotherapy and Its Predictors Among Women with Breast Cancer at the University of Gondar Compressive Specialized Hospital: A Retrospective Follow-Up Study - Zeleke Alem A (Dove Medical Press, 2020)
Adugnaw Zeleke Alem, Ejigu Gebeye Zeleke, Temesgen Yihunie Akalu Department of Epidemiology and Biostatistics, Institute of Public Health, College of Medicine and Health Science, University of Gondar, Gondar, EthiopiaCorrespondence: Adugnaw Zeleke Alem Email aduzeleke2201@gmail.comBackground: Early adjuvant chemotherapy improves the outcomes of breast cancer patients by increasing the benefit provided by the cytotoxic systemic therapies. Despite these, the recommended time to adjuvant chemotherapy and its predictors is very limited. Therefore, this study was determining the time to adjuvant chemotherapy and its predictors among women with breast cancer at the University of Gondar Comprehensive Specialized Hospital.Methods: An institution-based retrospective follow-up study was conducted at the University of Gondar Compressive Specialized Hospital from January 2015 to February 2019 among all women with breast cancer. Stata version 14 was used for data analysis. A stratified Cox regression model was fitted to identify the potential predictors. The adjusted hazard ratio (AHR) with a 95% confidence interval (CI) was reported to show the strength of the association. Cox–Snell residual test was used to check the goodness of fit.Results: In this study, the median time to adjuvant chemotherapy was 67 days with an interquartile range of 34– 102 days. More than three-fourth (79.9%) of patients received chemotherapy after 30 days. Of the total, 96.6% of patients with co-morbidity received adjuvant chemotherapy after 30 days. Regarding surgical complications, 97.0% of the patients with a surgical complications were received adjuvant chemotherapy after 30 days. Older patients (AHR= 0.34, 95% CI: 0.16,0.71), presence of co-morbidity (AHR= 0.43, 95% CI: 0.29, 0.62), positive surgical margin (AHR= 0.40, 95% CI: 0.25, 0.64), and presence of surgical complication (AHR= 0.55, 95% CI: 0.34, 0.88) were significantly associated with delayed time to adjuvant chemotherapy.Conclusion: In this study, time to adjuvant chemotherapy among women was longer. Age, co-morbidity, surgical complications, and margin status were significant predictors of time to adjuvant chemotherapy. Close follow-up is important for women with surgical complications, co-morbidities, elder patients, and patients with a positive margin.Keywords: adjuvant chemotherapy, breast cancer, survival analysis, Gondar